Representing lobola : exploring discourses of contemporary intersections of masculinity for Zimbabwean men in Cape Town : lobola, religion and normativity - Mwamanda, Sharon (African Gender Institute, 2016)
The following study is an exploration of religious Zimbabwean migrant men's representations of lobola. The study was undertaken to strengthen conversations about hegemonic masculinity which often marginalize both the role of religion in shaping masculinities and simultaneously may homogenize the notion of 'cultural tradition'. The research uses qualitative methods which seek to uncover the way in which Zimbabwean men who identify as Christian negotiate aspects of masculinity in relation to their lived experience of undertaking marriage through lobola. My main methodological aim was to allow participants to represent their own experiences, as these engage with both changing economic circumstances and Pentecostal Christianity. In order to analyse the empirical data I employ a theoretical framework which explores contextual and relational understandings of masculinity, religion and marriage. The dominant themes discussed include discourses on normativities; economic migration; religiosity and marriage which are used to further understand narratives of Zimbabwean men's lived experience of lobola. I argue that the negotiation of these intersectional aspects creates zones of tension which Zimbabwean men must negotiate with on an ongoing basis. The study argues that the past two decades of economic and political stress, coupled with a plethora of changing 'norms' about the meaning of heterosexuality, marriage, and partnership, mean that daily performativities of Christian-identified masculinity are both strongly embedded in fixed notions of gender normativity and simultaneously seek to accommodate changing circumstances.